2018
DOI: 10.1021/acs.nanolett.8b02968
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CRISPR-dCas9 on DNA with Solid-State Nanopores

Abstract: Solid-state nanopores have emerged as promising platforms for biosensing including diagnostics for disease detection. Here we show nanopore experiments that detect CRISPR-dCas9, a sequence-specific RNA-guided protein system that specifically binds to a target DNA sequence. While CRISPR-Cas9 is acclaimed for its gene editing potential, the CRISPR-dCas9 variant employed here does not cut DNA but instead remains tightly bound at a user-defined binding site, thus providing an excellent target for biosensing. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 23 publications
0
70
0
Order By: Relevance
“…Using nanopores as a sensing strategy enables detection of dsDNA without unzipping or temperature changes and also opens up opportunities for multiplexing. Yang et al showed that the binding position of the dCas9 effector protein could be deduced from the ionic current spike, which was later also confirmed by Weckman et al ( Weckman et al, 2019 ; Yang et al, 2018 ). The latter authors designed multiple crRNA sequences for dCas9 that could all bind to the same DNA sequence, creating ‘barcodes’ in the ionic current traces specific for the different DNA sequences.…”
Section: Crispr/cas Sensing In Poc Sensorsmentioning
confidence: 66%
See 2 more Smart Citations
“…Using nanopores as a sensing strategy enables detection of dsDNA without unzipping or temperature changes and also opens up opportunities for multiplexing. Yang et al showed that the binding position of the dCas9 effector protein could be deduced from the ionic current spike, which was later also confirmed by Weckman et al ( Weckman et al, 2019 ; Yang et al, 2018 ). The latter authors designed multiple crRNA sequences for dCas9 that could all bind to the same DNA sequence, creating ‘barcodes’ in the ionic current traces specific for the different DNA sequences.…”
Section: Crispr/cas Sensing In Poc Sensorsmentioning
confidence: 66%
“…Several sensor types have been created by researchers so far, in which no target-amplification is needed to measure at a very low LOD. These sensors are a graphene-based field effect transistor (gFET) ( Hajian et al, 2019 ), nanopore sensors ( Weckman et al, 2019 ; Yang et al, 2018 ), electrochemical sensors ( Bruch et al, 2019 ; Dai et al, 2019 ; Xu et al, 2020 ; D. Zhang et al, 2020 ) and a conductivity sensor combined with a DNA gel ( English et al, 2019 ).…”
Section: Crispr/cas Sensing In Poc Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanopores are promising tools for biosensing applications and sequencing of DNA and proteins, as they can resolve single analyte molecules, resolve structural modifications of molecules, and even discriminate between nucleotide sequences [1][2][3][4][5][6][7][8][9][10] . The detection mechanism is simple: while passing through the pore, a (part of a) molecule transiently blocks the ionic current, thereby inducing a small dip in the current signal, which is detectable by the electronics (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…38 Electrophoretic translocation of protein–DNA complexes through small nanopores (<3 nm diameter) typically results in the temporary trapping of the entire complex, which has allowed for the study of polymerase enzymes 39,40 and DNA-binding proteins. 41,42 Although promising, none of these approaches could efficiently control the trapping of the protein inside the nanopore or allow observation of enzyme kinetics or ligand-induced conformational changes.…”
mentioning
confidence: 99%